2005
DOI: 10.1002/esp.1207
|View full text |Cite
|
Sign up to set email alerts
|

The role of leaf inclination, leaf orientation and plant canopy architecture in soil particle detachment by raindrops

Abstract: A laboratory investigation of the effect of plant architecture on soil particle detachment by rainfall is described. The effects of leaf inclination, leaf orientation, effective canopy area, leaf area index, leaf subcatchment area, lowest canopy area, largest canopy area, canopy overlap area and an alternative leaf area index are examined using artificial plants. Detachment from a 30 cm diameter splash cup filled with sand (150 µ µ µ µ µm-1 mm particle size) was measured under three types of plant (small leave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 19 publications
1
19
0
Order By: Relevance
“…In such young forest stands horizontal tree characteristics seem to be of greater influence than vertical ones. This finding can support the key role of raindrop mass for rainfall erosivity over raindrop velocity being very low for small trees (Foot and Morgan, 2005;Goebes et al, 2014). Below small trees, however, small raindrop sizes can reach terminal velocity (de Moraes Frasson and Krajewski, 2011).…”
Section: Position Of Splash Cup In the Middle Of Four Tree Individualssupporting
confidence: 54%
“…In such young forest stands horizontal tree characteristics seem to be of greater influence than vertical ones. This finding can support the key role of raindrop mass for rainfall erosivity over raindrop velocity being very low for small trees (Foot and Morgan, 2005;Goebes et al, 2014). Below small trees, however, small raindrop sizes can reach terminal velocity (de Moraes Frasson and Krajewski, 2011).…”
Section: Position Of Splash Cup In the Middle Of Four Tree Individualssupporting
confidence: 54%
“…In this way, the impact speed and energy of the droplets impinging on the branches were reduced. Additionally, a wider spread of drop sizes is generated by the use of a screen, and drops are prevented from landing at the same locations below the drop‐formers (Imeson, ; Holden and Burt, ; Foot and Morgan, ; Clarke and Walsh, ). This modification of the experimental protocol was designed to suggest how stemflow generation might be affected by the presence of foliage, which also reduces the impact energy of drops on the branches sheltered below.…”
Section: Methodsmentioning
confidence: 99%
“…Although, this additional source of water is minor and mostly intercepted by 15 arbustive vegetation (Chuquiraga), other studies (Crockford and Richardson, 2000;Foot and Morgan, 2005) showed that the páramo ecosystem can catch low energy rain, drizzle and fog moisture on their leaves, which conduct over 50% of rainwater directly to the volcanic ash soils of Ecuadorian highlands (Janeau et al, 2015).…”
Section: Locationmentioning
confidence: 99%